Program Sakera Jempol (Sadari Kekerasan Perempuan dan Anak dengan Jemput Bola) Kabupaten Pasuruan Perspektif Yuridis - Hadaita Na'mah (State Islamic University (UIN) of Sunan Ampel, 2018)
This article examines the implementation of the Sakera Jempol program (Realizing the Violence of Women and Children with Ball Pick) in Pasuruan Regency and the Effectiveness of Law No. 23 of 2004 concerning the Elimination of Domestic Violence Against the Government’s Pasuruan Regency program. The data of this study are collected from observation, interviews, and documentation. Data are then analyzed using descriptive methods with inductive mindset, which describe the results of the research systematically and then seen using a juridical perspective. Based on data in the field, the Sakera Jempol Program is a program for handling victims of domestic violence, such as health services, counseling, rehabilitation, and legal assistance. The effectiveness of this program in reducing the number of violence, seen from the graph of the distribution of the number of cases of violence against women and children in the 2015-2018 period, succeeded in reducing cases from 68 cases to 21 cases of Domestic Violence (KDRT). The speed of handling victims of domestic violence is seen from the graph of the speed of handling cases of violence against women and children in the 2015-2018 period, from 5 days to 1 day. This program, if viewed from the reporting and protection stages, the handling phase, and the rehabilitation phase, is in accordance with Law No. 23 of 2004 concerning the Elimination of Domestic Violence.